2021
DOI: 10.1177/20503121211062793
|View full text |Cite
|
Sign up to set email alerts
|

Features associated with SARS-COV-2 positivity among people presenting with acute respiratory tract infections to public Hospitals in Harari region, Ethiopia

Abstract: Background: Despite investigating coronavirus among respiratory tract infected cases is a top priority to prevent further transmission, severe acute respiratory syndrome coronavirus 2 positivity among this group of patients remains unexplored in resource-limited settings. Therefore, this study intended to assess the severe acute respiratory syndrome coronavirus 2 positivity among patients presenting with acute respiratory tract infection from 1 July to 31 December 2020 in Harar Region, Ethiopia, from 15 Februa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
1
8
1
Order By: Relevance
“…This value is lower than that (21%, 21.2%, 22.9%, 28.3%, and 34.6%) reported in most other similar studies. 29 , 30 , 31 , 32 , 33 It is nevertheless similar to what was noted in California, Cairo, and Illinois 34 , 35 , 36 by Kim et al (9.5%), Fahim et al (12%), and Hazra et al (18.1%), respectively; and higher than that reported in Australia and southwest China. 21 , 25 Additionally, influenza and RSV were identified from patient samples and collectively contributed to 18.1% of all ILI cases in our study.…”
Section: Discussionsupporting
confidence: 83%
“…This value is lower than that (21%, 21.2%, 22.9%, 28.3%, and 34.6%) reported in most other similar studies. 29 , 30 , 31 , 32 , 33 It is nevertheless similar to what was noted in California, Cairo, and Illinois 34 , 35 , 36 by Kim et al (9.5%), Fahim et al (12%), and Hazra et al (18.1%), respectively; and higher than that reported in Australia and southwest China. 21 , 25 Additionally, influenza and RSV were identified from patient samples and collectively contributed to 18.1% of all ILI cases in our study.…”
Section: Discussionsupporting
confidence: 83%
“…In general, there seems to be agreement that infection rates considerably differ between urban and rural areas. Another interesting result is that education level did not affect reported transmissions and infections ( Bayode, et al, 2022 ; Birhanu, Ayana, Bayu, Mohammed, & Dessie, 2021 ).…”
Section: Findings and Discussionmentioning
confidence: 89%
“…Few studies ( ) were found addressing this continent. The focus is either on individual regions within a country, such as Angola ( Sebastião, et al, 2021 ); Nigeria ( Bayode, et al, 2022 ); Zambia ( Phiri, et al, 2021 ); and Ethiopia ( Birhanu, Ayana, Bayu, Mohammed, & Dessie, 2021 ), or cross-country assessments. Population density, per capita GDP and urbanization levels are found to be among the most commonly used groups of indicators.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hospital manages the referral cases received from the Eastern part of Oromia Region, Somali region, Harari region, and Dire Dawa City administration. The hospital has been labeled as COVID-19 treatment center by Ethiopian Minster of Health (MoH) since the outbreak of COVID-19 in Ethiopia [13] Participants and eligibility criteria An adult patient admitted to Hiwot Fana Specialized University Hospital with the diagnosis of COVID-19 between May 2020 and August 2021 was included in this study. The patient whose information was incomplete for the variable of interests was excluded from the study (Additional file 1).…”
Section: Study Setting and Designmentioning
confidence: 99%